2022
DOI: 10.1080/13510002.2022.2046423
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondrial reactive oxygen species in homeostasis regulation

Abstract: Mitochondria are the main source of reactive oxygen species (ROS) in cells. Early studies have shown that mitochondrial reactive oxygen species (mROS) are related to the occurrence and adverse outcomes of many diseases, and are thus regarded as an important risk factor that threaten human health. Recently, increasing evidence has shown that mROS are very important for an organism’s homeostasis. mROS can regulate a variety of signaling pathways and activate the adaptation and protection behaviors of an organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 109 publications
0
75
0
1
Order By: Relevance
“…In the 20 μg/mL NH 2 -PS NPs-treated groups, the examined genes including cycs , mt-co-1 , cox7a2, and slc25a4 showed a significant downward tendency ( Figure 5 i,k,l,n), indicating the potential risks of NH 2 -PS NPs to mitochondria function of HUVEC. Mitochondria are vital subcellular organelles to eukaryotic cells, which play valuable roles in energy production, ROS generation, and cellular signaling [ 37 ]. Therefore, we assessed the effects of PS NPs on the ATP production capacity.…”
Section: Resultsmentioning
confidence: 99%
“…In the 20 μg/mL NH 2 -PS NPs-treated groups, the examined genes including cycs , mt-co-1 , cox7a2, and slc25a4 showed a significant downward tendency ( Figure 5 i,k,l,n), indicating the potential risks of NH 2 -PS NPs to mitochondria function of HUVEC. Mitochondria are vital subcellular organelles to eukaryotic cells, which play valuable roles in energy production, ROS generation, and cellular signaling [ 37 ]. Therefore, we assessed the effects of PS NPs on the ATP production capacity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that resveratrol increased mitochondrial content in ECs. This was related with SIRT1 activation, further eNOS upregulation, and induction of mitochondrial biogenesis [ 54 ]. Resveratrol treatment also stimulated biogenesis of mitochondria in type 2 diabetic mice aortas [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was related with SIRT1 activation, further eNOS upregulation, and induction of mitochondrial biogenesis [ 54 ]. Resveratrol treatment also stimulated biogenesis of mitochondria in type 2 diabetic mice aortas [ 54 ]. However, manipulating the mitochondrial function may also be unfavorable in ECs, due to mitochondrial ROS (mROS) production [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to a sudden change of environmental conditions typically induces stress reactions in organisms to counteract and prevent irreversible damage of cells, tissues or organs. Stabilization of metabolism plays a central role in such stress response because it is preliminary to perceive and integrate environmental signals (Zhang et al, 2022). Stability properties of a biochemical reaction network can be quantified via an SKM approach (Steuer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%